Side Effects of Using Depo Medroxy Progesterone Acetate Contraceptive Contraceptives in Midwife Practices - Ni Wayan Kusmiati; Putu Sukma Megaputri (LPPM UIKA Bogor, 2023)
Injectable contraception is the most choice used by women of childbearing age as a delay in pregnancy or termination of pregnancy. Many acceptors do not know optimally about the side effects that are often felt by mothers who use contraception. The purpose of this study was to identify the side effects felt by mothers using 3-month injectable contraception. This research method is descriptive quantitative with cross sectional approach. The sampling technique in this study was purposive sampling with a total sample of 67 respondents. The results of the study reported that the side effects experienced were that the mother felt that she had difficulty having menstruation (87.9%), then the mother did not experience menstruation while using DMPA (84.8%), the mother felt there was an increase in fat (40.9%), an increase in body weight (40.9%). Furthermore, none of the acceptors felt a decrease in activity, acne, vaginal discharge, hair loss and menstruation that was faster than usual.